Pengaruh PDB, Neraca Perdagangan, Inflasi, Suku Bunga dan Jumlah Uang Beredar Terhadap Nilai Tukar Rupiah - Rizka Cahyarani (Tauhidinomics: Journal of Islamic Banking and Economics, 2026)
Exchange rate movements reflect economic performance and are influenced by both domestic and external factors. This study examines the impact of GDP, trade balance, inflation, interest rates, and money supply on the Indonesian rupiah exchange rate from 2010–2024 using quarterly data and a Vector Error Correction Model (VECM). The results show that GDP, trade balance, and inflation significantly affect the exchange rate in the long run, while interest rates and money supply do not. These findings suggest that exchange rate stability depends more on macroeconomic fundamentals, implying that policymakers should prioritize growth, trade performance, and inflation control, supported by a broader policy mix beyond conventional monetary tools.